1985
DOI: 10.1111/j.1475-2743.1985.tb00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term rates of acidification of UK upland acidic soils

Abstract: The approximate time-scales for serious lowering of the base status of acidic upland soils in northeast Scotland have been based on assessments of geochemical weathering rates in two upland catchments. Periods of 1100 and 12000 years are obtained for soils evolved primarily from granite and quara-biotite-norite respectively. Factors regulating the rate of removal ofbase cations in drainage water are discussed, to elucidate those which significantly influence long-term rates of soil acidification. The relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Comparisons of weathering-derived outputs of calcium from catchments in NE Scotland on predominantly granite (Glendye) and the much more basic quartz-biotite-norite (Peatfold, Clenbuchat) showed little difference (Creasey et al 1986). This finding suggested that typical lower to middle altitude upland soils on moderate slopes in NE Scotland should reach the deep hill peat formation stage after c. 11,000 years of post-glacial weathering for granite, and c. 22,000 years for the more basic parent material (Edwards 1985b). These estimates suggest that the soils derived from granite, and hence the waters draining from them, should be in the latter stages of acidification and on the threshold (or beyond it) of becoming very susceptible to acidifying pollutant effects.…”
Section: Relevant Soil Formation Processesmentioning
confidence: 97%
“…Comparisons of weathering-derived outputs of calcium from catchments in NE Scotland on predominantly granite (Glendye) and the much more basic quartz-biotite-norite (Peatfold, Clenbuchat) showed little difference (Creasey et al 1986). This finding suggested that typical lower to middle altitude upland soils on moderate slopes in NE Scotland should reach the deep hill peat formation stage after c. 11,000 years of post-glacial weathering for granite, and c. 22,000 years for the more basic parent material (Edwards 1985b). These estimates suggest that the soils derived from granite, and hence the waters draining from them, should be in the latter stages of acidification and on the threshold (or beyond it) of becoming very susceptible to acidifying pollutant effects.…”
Section: Relevant Soil Formation Processesmentioning
confidence: 97%
“…However, under pristine conditions the BC and alkalinity fluxes passing through upland soils may massively exceed the corresponding fluxes estimated by assuming that all water infiltrates vertically. This would have a beneficial effect on soil base status down slope for thousands of years (Edwards, Creasey, Skiba, Peirson-Smith, & Cresser, 1985). The "damage" being done to soils at the foot of slopes at the "final" equilibrium would thus be far greater than that done up slope.…”
Section: In Uplands If Alkalinity Is Transferred Down Slope Naturallmentioning
confidence: 99%
“…The kappa statistic [37] will be calculated, which measures the level of agreement between reviewers. If kappa is less than 0.6, the reviewers will discuss the discrepancies and clarify the interpretation of the inclusion criteria.…”
Section: Study Inclusion Criteria and Study Collectionmentioning
confidence: 99%